Genetic associations of perinatal pain and depression. (October 2019) - McClain, Lora; Farrell, Lia; LaSorda, Kelsea; Pan, Lisa A.; Peters, David; Lim, Grace
Underlying genetic influences may affect perinatal pain, depression, or both. We investigated the role of 59 single-nucleotide polymorphisms on 20 quantitative traits measured in perinatal women. Moreover, 183 pregnant women (28–37 weeks' gestation) were prospectively genotyped for single-nucleotide polymorphisms with known prior associations with either pain or depression in nonpregnant populations. Prenatal saliva samples were collected. Phenotypic data were gathered during prenatal, labor and delivery, and postpartum (six weeks and three months) periods, capturing labor pain, Edinburgh Postnatal Depression Score, and Brief Pain Inventories. Following quality control, genotypes were used as predictors and phenotypes as dependent variables in multiple linear regression analyses to detect associations. Three statistical models were tested: additive allele effects, deviation from dominant allele effects, and the joint test of both. rs4633 (a synonymous single-nucleotide polymorphism in COMT ) associated with "pain right now" scores at six weeks postpartum. Single-nucleotide polymorphisms rs1135349 (a single-nucleotide polymorphism within a small noncoding RNA that has many prior associations for depression) and rs7548151 (intronic in ASTN1 ) were associated with the maximum pain unpleasantness score experienced during labor (a measure of the emotional valence of labor pain), controlling for the Holm–Bonferroni family-wise error rate. Sensory dimensions of labor pain (i.e., pain intensity) and postpartum depression scores were not associated with genotyped single-nucleotide polymorphisms. Identifying genomic components of these perinatal complex disorders may produce insights into relevant pathways or novel treatment options.